2019
DOI: 10.1097/iop.0000000000001231
|View full text |Cite
|
Sign up to set email alerts
|

Septic Cavernous Sinus Thrombosis Associated With Orbital Cellulitis: A Report of 6 Cases and Review of Literature

Abstract: Purpose: To describe risk factors, clinical parameters, treatment, and prognosis for patients with septic cavernous sinus thrombosis presenting with orbital cellulitis. Methods: Retrospective case series of 6 patients identified with septic cavernous sinus thrombosis and orbital cellulitis confirmed by magnetic resonance imaging at a tertiary care center from January 1980 to December 2016. Medical records were reviewed for demographics, risk factors, sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 92 publications
0
33
0
1
Order By: Relevance
“…One retrospective review has shown that antibiotic treatment in combination with early anticoagulation therapy reduces the morbidity associated with blindness, stroke, and ophthalmoplegia, among other complications 17 . Other retrospective reviews have indicated that anticoagulation therapy is safe in CST after the exclusion of patients with intracranial hemorrhage and other possible bleeding disorders 7 . Anticoagulation therapy was not administered to the patient in the present case out of concern for the potential risk of hemorrhage and further extension of the septic emboli.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…One retrospective review has shown that antibiotic treatment in combination with early anticoagulation therapy reduces the morbidity associated with blindness, stroke, and ophthalmoplegia, among other complications 17 . Other retrospective reviews have indicated that anticoagulation therapy is safe in CST after the exclusion of patients with intracranial hemorrhage and other possible bleeding disorders 7 . Anticoagulation therapy was not administered to the patient in the present case out of concern for the potential risk of hemorrhage and further extension of the septic emboli.…”
Section: Discussionmentioning
confidence: 77%
“…Both bacteria and fungi have been shown to cause CST. The most common causative bacterial pathogens are Staphylococcus aureus (60%–70%), Streptococcus (17%), gram‐negative bacteria (5%), and Pneumococcus (5%), whereas the most common pathogenic fungal infections that could result in CST include those caused by Rhizopus and Absidia and mucormycosis (most frequently seen in patients with diabetes) 7,8 . In this patient, the blood cultures that were grown before antibiotic use revealed the presence of S .…”
Section: Discussionmentioning
confidence: 88%
“…Other data are narrowing of the ipsilateral intracranial internal carotid artery, and enhancement of the arterial wall. Ischemic strokes or cerebral hemorrhages may be noted [ 19 , 20 , 21 , 22 , 23 ].…”
Section: ⧉ Discussionmentioning
confidence: 99%
“…There are also Streptococcus pneumoniae, Gram-negative bacilli, and anaerobes present. Fungi, which include Aspergillus and Rhizopus species, are a less common pathogen [9][10]. Henry Gray (1918) Anatomy of the Human Body.…”
Section: Discussionmentioning
confidence: 99%
“…The cavernous sinuses are trabeculated cavernous cavities generated by the layers of dura mater and filled with venous blood (one on each side of the sella turcica, above and lateral to the sphenoid sinuses, anteriorly superior orbital fissure, and posteriorly petrous section of the temporal lobe). The superior and inferior ophthalmic veins, as well as the superficial cortical veins, drain into the basilar plexus anteriorly, whereas the superior and inferior petrosal sinuses drain into the basilar plexus posteriorly [ 8 - 10 ]. The close proximity of veins, arteries, nerves, meninges, and paranasal sinuses contributes to the development and presentation of CST as can be observed from Figure 1 .…”
Section: Discussionmentioning
confidence: 99%